Economists' Perception of Minority Economic Problems: A View of Emerging Literature - Brimmer, Andrew F.; Harper, Harriett (Journal of Economic Literature, 1970)
W ITH MUCHI of the nation's attention focused on poverty and minority problems in the 1960s, what effort was made by professional economists to study and report on the economic aspects of these problems? What areas of minority problems have been of interest to economists? To answer these questions a survey of the joumal literature was undertaken in late 1969 and further extended in the early months of 1970. The results clearly show that economists are devoting increased attention to the economic problems of minority groups. At the same time, however, it is also clear that this range of problems remains far from the central concern of the profession. In general, the most activity-judging from the published record-seems to be in the fields of microeconomic theory, international economics, and monetary economics. Yet, in the last few years, there has been a much sharper focus on education, welfare theory, and poverty. It is this latter focus that has led to a broader consideration of economic problems of minority groups. Certain aspects have been of much greater interest to economists, such as labor and employment-largely, no doubt, because it is in these areas that larger amounts of disaggregated data by race have been available traditionally. New areas which need more-and which have received little -assessment by economists are black capitalism, urban economics, and the economic aspects of crime and social disorganization.